Use of a modified version of the switching verbal fluency test for the assessment of cognitive flexibility - Paula,Jonas Jardim de (2015)
Objective: Verbal fluency tests are widely used for the assessment of executive functions. However, traditional versions of the test depend on several cognitive factors beyond these components. The aim of this study was to evaluate the associations of a modified version of the verbal fluency with specific measures of executive functions. Methods: Sixty adults were evaluated using traditional versions of verbal fluency (animals/fruits) and a modified condition where subjects must switch between animals and fruits. Processing speed, semantic abilities, psychiatric symptoms and executive functions were also assessed. Results: Partial correlations between the verbal fluency tests and measures of executive functions, controlled for demographic, cognitive and psychiatric symptoms, suggest that cognitive flexibility has 9% shared variance with the verbal fluency test - category animals, 2 % with category fruits, 8% with total words in switching condition, and 20% with total correct word-pairs produced in switching condition. The other aspects of executive functions during the task had shared variance of between 1% and 7% with the verbal fluency tasks. Conclusion: The results suggest that correct word-pairs produced in switching verbal fluency may be a more specific measure for evaluating cognitive flexibility compared to other versions of verbal fluency.